(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
To the successful and sustained development of Indian banks, it is basic to make a pool of competent and committed administrative personnel who can work with an aim to further the objectives of the Institution. This can be achieved if they can function in an environment of freedom in decision-making processes. Innovative methods of operations and management of a Bank can bring competitive edge and thereby great amount of job satisfaction among its personnel. Since employee satisfaction affects their performance and commitment, which has a bearing on the banks’ growth and profitability, no banking organization, can risk itself to ignore it. This paper attempts to look at experimentally whether Intraprenuerial condition in keeping banking organizations encourages managerial satisfaction. The sample study is carried out through a structured questionnaire developed to elicit the responses from the respondent- managers of SBI working in Delhi.